Strategic workforce planning in health and social care – an international perspective: A scoping review. (June 2023) - Sutton, Claire; Prowse, Julie; McVey, Lynn; Elshehaly, Mai; Neagu, Daniel; Montague, Jane; Alvarado, Natasha; Tissiman, Chris; O'Connell, Kate; Eyers, Emma; Faisal, Muhammad; Randell, Rebecca
Highlights: Workforce modelling for prediction is discussed in 66 of 101 references. Workload Indicators of Staffing Needs (WISN) is used worldwide for staffing requirement. The differentiated medical workforce is privileged in supply/demand projections. Unregistered workers are poorly represented and planned for. There is minimal consideration of health and social care as one workforce. Abstract: Effective strategic workforce planning for integrated and co-ordinated health and social care is essential if future services are to be resourced such that skill mix, clinical practice and productivity meet population health and social care needs in timely, safe and accessible ways globally. This review presents international literature to illustrate how strategic workforce planning in health and social care has been undertaken around the world with examples of planning frameworks, models and modelling approaches. The databases Business Source Premier, CINAHL, Embase, Health Management Information Consortium, Medline and Scopus were searched for full texts, from 2005 to 2022, detailing empirical research, models or methodologies to explain how strategic workforce planning (with at least a one-year horizon) in health and/or social care has been undertaken, yielding ultimately 101 included references. The supply/demand of a differentiated medical workforce was discussed in 25 references. Nursing and midwifery were characterised as undifferentiated labour, requiring urgent growth to meet demand. Unregistered workers were poorly represented as was the social care workforce. One reference considered planning for health and social care workers. Workforce modelling was illustrated in 66 references with predilection for quantifiable projections. Increasingly needs-based approaches were called for to better consider demography and epidemiological impacts. This review's findings advocate for whole-system needs-based approaches that consider the ecology of a co-produced health and social care workforce.